Influence of FDI Inflows on Income Inequality Through the Moderating Role of Governance in Arab Countries - Alotaibi, Mashael Mohammad; Theng, Lau Wei; Muhammad, Haslinah Bt; Ni, Soh Wei (Advances in Social Sciences Research Journal, 2025)
This study investigates the relationship between Foreign Direct Investment (FDI) and income inequality in Arab countries, emphasizing the moderating role of governance, specifically corruption control and political stability. Using panel data analysis, the research assesses how variations in governance impact the effects of FDI on income distribution across these nations. Theoretical frameworks such as modernization theory, dependency theory, and world-systems theory guide the examination of whether robust governance can mitigate the potential negative impacts of FDI on economic disparities. The findings indicate that FDI tends to exacerbate income inequality in settings with weak governance. However, in environments where governance mechanisms are strong, the adverse effects of FDI on income distribution are significantly reduced. These results highlight the dual role of FDI in promoting economic growth and contributing to income disparity, contingent on the quality of governance. This research provides empirical evidence on the conditional impacts of FDI, underscoring the critical role of governance in achieving equitable economic outcomes from foreign investments. The insights are particularly relevant for policymakers aiming to leverage FDI effectively within development strategies that prioritize social equity and economic inclusivity. The study suggests that future research might explore the long-term impacts of FDI and delve deeper into the nuanced interactions between governance quality and economic development in the Arab world.